Exploring the relationship between physical activity and sleep quality: insights from Indonesia university students / Muhammad Nur Amin Salleh, Nur Dalilah Dahlan and Muhammad Wafi A. Rahman - Salleh, Muhammad Nur Amin; Dahlan, Nur Dalilah; A. Rahman, Muhammad Wafi (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Physical inactivity and poor sleep quality are growing public health concerns, particularly among university students [1]. This study examines the relationship between physical activity and sleep quality among Faculty of Sports and Health Education (FPOK) students at Universitas Pendidikan Indonesia [2]. By assessing activity levels, sleep quality, and gender differences, the research aims to provide insights into lifestyle behaviors affecting student well-being and academic performance, emphasizing the need for targeted health interventions [3]. This study employed a stratified sampling technique, selecting 341 FPOK students from four academic programs at UPI Bandung. Physical activity levels were assessed using the International Physical Activity Questionnaire (IPAQ), categorizing participants into high, moderate, or low activity levels. Sleep quality was measured using the 28-item Sleep Quality Scale (SQS). Data were collected through self-reported questionnaires, ensuring a representative sample for analysis.